Participatory design with teenagers for cyberbullying prevention and mitigation - Almeida, André Filipe Pereira de; Villela, Maria Lúcia Bento; Santos, Caroline Queiroz; Guimarães, Gabryella Castro (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2022)
Despite being a serious problem among teenagers, brought by the wide use of social media platforms, little has been explored about the development and use of technological tools to support the mitigation of cyberbullying in schools. Particularities that involve the occurrence of cyberbullying in online social networks can explain this scarcity. In this context, our study applies Participatory Design techniques to two groups of high school students. During four design sessions carried out remotely, participants shared their experiences with cyberbullying and designed potential solutions to prevent and mitigate it through three low-fidelity prototypes. The discussions around these prototypes suggest that schools still have a long way to go in dealing with this type of violence. However, it is possible to reach victims, aggressors, and bystanders through technological resources, constituting an essential step toward preventing and combating cyberbullying among teenagers.